The Relationship Between the Use of Gadgets During the Covid-19 Pandemic on Personal Social and Language Development in Children Aged 4-6 Years - Zahwa Octri Muslimah; Agus Saptanto; Kanti Ratnaningrum (Future Science, 2025)
The use of gadgets during the COVID-19 pandemic has increased in children aged 4-6 years. Excessive use of gadgets causes addiction, especially with access to harmful content, such as violent scenes that children see in games and content in applications that are believed to affect children's social and language skills. It is known that the early age is a conducive period for developing various aspects of important skills in children such as personal social abilities, intelligence, talents, physical abilities, language, socio-emotional, and spiritual quotient. However, the increased use of gadgets is known to affect children's personal, social, and language development. This study used a qualitative approach using phenomenological methods. This research aims to determine and analyze the relationship between gadget use during the COVID-19 pandemic and personal social and language development in children aged 4-6. In the personal social aspect, there was a negative development where children could not help themselves and self-manage, interact less with their surroundings, and became less responsive. There was also a negative development in language where children became less likely to communicate, were influenced by foul language, and could not express their ideas. Interestingly, these children were able to absorb new vocabulary in foreign languages more quickly and were full of knowledge with a positive imagination. We discovered that an increasing duration of gadget use leads to negative manifestations in the personal and social development of children. However, there was also a positive aspect of gadget use especially regarding creativity and imagination. Therefore, it is necessary to control, supervise, and utilize applications on gadgets to optimize the development of both the language and personal social of children who are excessively exposed to gadgets.